Structural Based Analyses of the JC Virus T-Antigen F258L Mutant Provides Evidence for DNA Dependent Conformational Changes in the C-Termini of Polyomavirus Origin Binding Domains. - Gretchen Meinke; Paul J Phelan; Jong Shin; David Gagnon; Jacques Archambault; Andrew Bohm; Peter A Bullock (PLoS Pathogens)
The replication of human polyomavirus JCV, which causes Progressive Multifocal Leukoencephalopathy, is initiated by the virally encoded T-antigen (T-ag). The structure of the JC virus T-ag origin-binding domain (OBD) was recently solved by X-ray crystallography. This structure revealed that the OBD contains a C-terminal pocket, and that residues from the multifunctional A1 and B2 motifs situated on a neighboring OBD molecule dock into the pocket. Related studies established that a mutation in a pocket residue (F258L) rendered JCV T-ag unable to support JCV DNA replication. To establish why this mutation inactivated JCV T-ag, we have solved the structure of the F258L JCV T-ag OBD mutant. Based on this structure, it is concluded that the structural consequences of the F258L mutation are limited to the pocket region. Further analyses, utilizing the available polyomavirus OBD structures, indicate that the F258 region is highly dynamic and that the relative positions of F258 are governed by DNA binding. The possible functional consequences of the DNA dependent rearrangements, including promotion of OBD cycling at the replication fork, are discussed.